Adenosine-A2A Receptor Signaling Plays a Crucial Role in Sudden Unexpected Death in Epilepsy - Shen, Hai-Ying; Baer, Sadie B.; Gesese, Raey; Cook, John M.; Weltha, Landen; Coffman, Shayla Q.; Wu, Jie; Chen, Jiang-Fan; Gao, Ming; Ji, Teng (Frontiers in Pharmacology, 2022)
Adenosinergic activities are suggested to participate in SUDEP pathophysiology; this study aimed to evaluate the adenosine hypothesis of SUDEP and specifically the role of adenosine A2A receptor (A2AR) in the development of a SUDEP mouse model with relevant clinical features. Using a combined paradigm of intrahippocampal and intraperitoneal administration of kainic acid (KA), we developed a boosted-KA model of SUDEP in genetically modified adenosine kinase (ADK) knockdown (Adk+/-) mice, which has reduced ADK in the brain. Seizure activity was monitored using video-EEG methods, and in vivo recording of local field potential (LFP) was used to evaluate neuronal activity within the nucleus tractus solitarius (NTS). Our boosted-KA model of SUDEP was characterized by a delayed, postictal sudden death in epileptic mice. We demonstrated a higher incidence of SUDEP in Adk+/- mice (34.8%) vs WTs (8.0%), and the ADK inhibitor, 5-Iodotubercidin, further increased SUDEP in Adk+/- mice (46.7%). We revealed that the NTS level of ADK was significantly increased in epileptic WTs, but not in epileptic Adk+/- mutants, while the A2AR level in NTS was increased in epileptic (WT and Adk+/-) mice vs non-epileptic controls. The A2AR antagonist, SCH58261, significantly reduced SUDEP events in Adk+/- mice. LFP data showed that SCH58261 partially restored KA injection-induced suppression of gamma oscillation in the NTS of epileptic WT mice, whereas SCH58261 increased theta and beta oscillations in Adk+/- mutants after KA injection, albeit with no change in gamma oscillations. These LFP findings suggest that SCH58261 and KA-induced changes in local neuronal activities in the NTS of epileptic mice. Together, we revealed a crucial role for NTS A2AR in SUDEP pathophysiology suggesting A2AR as a potential therapeutic target for SUDEP risk prevention.